Cruciform Theology and its Implications for African Christianity - Isaac Boaheng (E-Journal of Religious and Theological Studies)
Christianity has, since the beginning of the 20th century, experienced an unmatched numerical growth in Africa. Presently, Africa occupies a central position in global Christianity, as evidenced by the active involvement of numerous African churches in reverse missions to areas like Europe and North America. The proliferation of the church in Africa has given rise to a cadre of theologians and biblical scholars who engage in diverse theological inquiries to enhance the qualitative growth of the church. However, despite their diligent efforts, the impact of African theologians and biblical scholars on the church and society is limited because most African biblical scholars fail to focus on the cross. The need for a cross-informed theology has prompted this paper which explored how cruciform theology might affect evangelical Christianity and the society. This paper further explored the implications for contextualizing theology, responsibly exercising political power, and practicing effective stewardship within the African context. The paper used a qualitative research approach to collect primary data from books, journal articles, and theses/dissertations on the subject matter. Using a descriptive approach, this paper sought to reconstruct cruciform theology for African evangelicals and to draw lessons for Christianity in Africa. The main argument is that the cross should be at the heart of every dimension of the church’s existence, ultimately leading to the transformation of society. The goal of this study is to encourage ongoing dialogue and reflection on the theology of the cross among the African Evangelical Christian community.